STRATEGI PEMBERDAYAAN PEREMPUAN MELALUI PENGELOLAAN BANK SAMPAH SARASWATI CIPETE UTARA - Tedi Tedi Tedi (Masyarakat Madani: Jurnal Kajian Islam dan Pengembangan Masyarakat, 2020)
This study discusses the empowerment of women initiated and proclaimed by the North Cipete Saraswati Garbage Bank. This study aims to determine what and how the women's empowerment strategies are carried out by the movement. In practice, this study uses qualitative methods through observation and interview techniques, in which researchers take part in the entire process of searching for information and data needed. The subjects of the informants in this study were the management and active members of the waste bank. The results of the study show that the waste bank program is considered effective because it supports all aspects of women's empowerment in it according to the existing theory.